2013
DOI: 10.2147/jpr.s32299
|View full text |Cite
|
Sign up to set email alerts
|

Postamputation pain: epidemiology, mechanisms, and treatment

Abstract: Postamputation pain (PAP) is highly prevalent after limb amputation but remains an extremely challenging pain condition to treat. A large part of its intractability stems from the myriad pathophysiological mechanisms. A state-of-art understanding of the pathophysiologic basis underlying postamputation phenomena can be broadly categorized in terms of supraspinal, spinal, and peripheral mechanisms. Supraspinal mechanisms involve somatosensory cortical reorganization of the area representing the deafferentated li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
162
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(168 citation statements)
references
References 134 publications
1
162
1
4
Order By: Relevance
“…Choi et al [14] reported that the occurrence of chronic pain after spine surgery was approximately 20%, and this incidence is lower than the 32% following discectomy and up to 85% observed after amputation. [2527] If the theory proposed by Eipe et al [24] is correct, then the lower incidence of chronic pain after spine surgery may explain why pregabalin failed to demonstrate efficacy in patients undergoing spine surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Choi et al [14] reported that the occurrence of chronic pain after spine surgery was approximately 20%, and this incidence is lower than the 32% following discectomy and up to 85% observed after amputation. [2527] If the theory proposed by Eipe et al [24] is correct, then the lower incidence of chronic pain after spine surgery may explain why pregabalin failed to demonstrate efficacy in patients undergoing spine surgery.…”
Section: Discussionmentioning
confidence: 99%
“…7 The neuroma’s afferent fibers develop ectopic activity, mechanical sensitivity, and chemosensitivity to catecholamines. 8 The altered expression of transduction molecules, upregulation of sodium channels, downregulation of potassium channels, and development of nonfunctional connections between axons all contribute to the hyperexcitability and spontaneous discharge witnessed within injured nerves. 9 Nonsurgical treatment includes desensitization, chemical or anesthetic injections, transcutaneous electrical nerve stimulation, topical lidocaine, and adjuvant pain medications such as antidepressants and anticonvulsants.…”
mentioning
confidence: 99%
“…7 Fibrin patch application with placement of a local pain catheter has also been described. 16 The long-term outcomes of such methods are mixed, 6,8 likely because of the nonphysiological nature of these treatments.…”
mentioning
confidence: 99%
“…Following limb loss, almost everyone experiences phantom limb sensations, which include the perception of itching, pressure, or temperature changes in the phantom limb, as well as an awareness of its orientation in space (2). Furthermore, reports estimate that 85% of all persons with amputation experience painful sensations, or phantom limb pain (PLP), either immediately following amputation or within days to weeks post-operation (3). For many, both phantom sensations and PLP are bothersome and even disabling, interfering with the ability to live independently and further emphasizing the need for successful treatment interventions.…”
Section: Introductionmentioning
confidence: 99%